Pengaruh Dosis Kasgot Limbah Hotel Terhadap Pertumbuhan Dan Hasil Tanaman Pakcoy (Brassica rapa L.) Varietas Nauli F1 - Abdullah, Rohana; Pratama, Junjun; Aisyah, Iis (Fakultas Pertanian Universitas Winaya Mukti, 2023)
This research was conducted in polybags with Andisol soil type in the Experimental Garden of the Faculty of Agriculture, University of Winaya Mukti, Tanjungsari District, Sumedang Regency from June to July 2021. The purpose of this study was to see how the best of hotel food waste BSF frass affected the growth and yield of pakcoy (B. rapa L.). The research utilized a Randomized Block Design with six treatments: A = 0 ton.ha-1 (without BSF frass/control), B= 3 ton.ha-1 cow dung compost, C =1,5 ton.ha-1 BSF frass, D = 3 ton.ha-1 BSF frass, E = 4.5 ton.ha-1 BSF frass, and F = 6 ton.ha-1 BSF frass, all of which are repeated four times.The use of hotel waste BSF frass had a substantial impact on plant height, leaf number, root volume, canopy fresh weight, root fresh weight, canopy dry weight, and root dry weight, according to the findings. Treatment F (6 ton.ha-1) had the best results in terms of plant height, number of leaves, root volume, crown fresh weight, root fresh weight, and canopy dry weight, according to the study's findings. Treatment E (4.5 tons.ha-1) produced the best results in terms of root dry weight.